HEGEMONIC RELATIONS IN GENDERING THE TECHNOLOGY: The Case of Apple’s @idevice.indonesia Community - Kania, Dessy (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
This article dissects the practice of gender typification of the iPhone through three layers and explore how the hegemonic relationship between Apple, the community; the moderator and its members. Combining Judith Williamson's semiotics approach and the theory of encoding-decoding from Stuart Hall, it was found that there were differences in gender construction between Apple and the moderator of @idevice.indonesia community and its members. Apple has never explicitly proclaimed the iPhone as a sexed product, if so they have used subtle gender typifications through color coding, objects, and design. Whereas the @ idevice.indonesia community and members, carry out gender typification closely with stereotypes within patriarchal culture. This finding explains that prosumer such as @ idevice.indonesia community and its member has benefited Apple because as a producer, they continues to echoes iPhone through various uploads and comments on Instagram @ idevice.indonesia. On the other hand, prosumer was detrimental to Apple in terms of ideology because it destitute the gender awareness and gender bender ideas that Apple has carried throughout the iPhone’s marketing effort. The @ idevice.indonesia community and its member has ultimately looked at iPhone as a feminine product in a binary gender perspective. To cite this article (7th APA style):Kania, D. (2021). Hegemonic Relations in Gendering the Technology: The Case of Apple’s @idevice.indonesia Community. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(1), 39-51. http://dx.doi.org/10.36782/jcs.v1i1.2098